Synthesis of SiC whiskers by VLS and VS process. Issue 5 (April 2016) - Li, Xiang; Zhang, Guangqing; Tronstad, Ragnar; Ostrovski, Oleg
Abstract: This study investigates the mechanisms of SiC whisker formation in the carbothermal reduction of quartz to SiC in different gas atmospheres. Reduction of quartz by graphite was studied in Ar, H2, and CH4 –H2 –Ar gas mixture in a laboratory fixed bed reactor. The reduction products were characterised by XRD, SEM and TEM. Whiskers were not formed in the carbothermal reduction of quartz in argon. Two types of SiC whiskers were observed in the carbothermal reduction of quartz in H2 and CH4 –H2 –Ar gas mixture. In the process of reduction at 1400–1600 °C in H2 and at 1200–1600 °C in CH4 –H2 –Ar gas mixture, whiskers with hexagonal shape with diameter 100–800 nm and length up to tens of microns were formed by the VLS mechanism under catalytic effect of iron. The whiskers with the characteristics of cylindrical shape and high aspect ratio were synthesized in CH4 –H2 –Ar gas mixture at 1400–1600 °C by VS mechanism.